1982
DOI: 10.1021/j100222a005
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the initial reaction of nitrite ion in bisulfite solutions

Abstract: The kinetics of the reaction of nitrite ion in bisulfite solutions to form hydroxylaminedisulfonate have been investigated. Evidence has been presented that nitrososulfonic acid is the probable intermediate in this reaction and that it can undergo sulfonation or hydrolysis reactions. The hydrolysis reaction yields N20 under the present conditions of study (acid solutions), which complicates the determination of the rate of formation of hydroxylaminedisulfonate. The ratio of the rate constants for sulfonation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
58
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 3 publications
9
58
1
Order By: Relevance
“…This involves applying the rate expression for reaction (R1) with Henry's law and acid dissociation constants computed at 271 K (Supplementary Table 1). We find a fogwater nitrite (N(III), mainly as NO 2 − ) concentration of 2.2 μmol L −1 , which leads to an e-folding SO 2 lifetime of 3.8 h using the rate expression of Martin et al 28 extended to pH 5.7 but 79 h using the rate expression of Oblath et al 27 . The former would imply a major role of HONO as SO 2 oxidant while the latter would imply an insignificant role.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…This involves applying the rate expression for reaction (R1) with Henry's law and acid dissociation constants computed at 271 K (Supplementary Table 1). We find a fogwater nitrite (N(III), mainly as NO 2 − ) concentration of 2.2 μmol L −1 , which leads to an e-folding SO 2 lifetime of 3.8 h using the rate expression of Martin et al 28 extended to pH 5.7 but 79 h using the rate expression of Oblath et al 27 . The former would imply a major role of HONO as SO 2 oxidant while the latter would imply an insignificant role.…”
Section: Resultsmentioning
confidence: 80%
“…where k 1 = 142 M −3/2 s −1 . Another study by Oblath et al 27 gives a rate expression chemistry, as is frequently observed in polluted air masses 34,35 . The signature of the reaction (R1) taking place in Stage II would then be manifested by the step increase in N 2 O between the two Stages.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[1981] and Oblath et al [1981Oblath et al [ , 1982, who performed experi- ground atmosphere leading to a fall in H20 2 and HONO concentration with a corresponding decrease in the oxidation rate.…”
Section: Soz + Hono Reaction In Hzsomentioning
confidence: 99%
“…The redox reaction of HONO and SO 2 results in S(VI) and HON, which undergoes fast secondary reactions such as dimerization /dehydration to result in N 2 O [16]. The Raschig mechanism (Scheme I) describes the reduction of HONO by bi-sulfite ion leading to an initial adduct nitroso-sulfonate ( ) which further reacts with an additional bi-Ϫ ONSO 3 sulfite ion to form hydroxylaminedisulfonate (HADS) or undergoes hydrolysis to form nitroxyl (HON) in a competitive reaction [20,21]. Nitroxyl is a key intermediate of N(+I) leading to nitrous oxide and its dehydrative dimerization to N 2 O occurs in solution, but the corresponding rate constant was not accurately estimated [22,23].…”
Section: Introductionmentioning
confidence: 99%